EFFICIENCY MONITORING: AN INSTRUMENT FOR REDUCTION OR AN ENGINE FOR GROWTH? - Sergey G. Prokhorov; Anna A. Svirina; Aleksey I. Chekhonadskikh (Высшее образование в России)
The paper analyzes indicators used in higher education institution monitoring from the point of view of estimation the goals of monitoring. It is suggested that monitoring results can be efficiently used to define higher education growth engines, and not only to estimate directions of educational institution reduction. The authors come to a conclusion that the monitoring procedure needs further improvement. First of all it is necessary to define the goals of monitoring and to explicate the meaning of the indices used.